Skyhook-PID Control Strategy to Improve Performance of a Pneumatic Active Suspension System - Gigih Priyandoko (Widyagama University of Malang, 2020)
The research applies a skyhook-PID control method for an active suspension system. The control strategy has three feedback control loops. They are the innermost loop for the force tracking of the pneumatic actuator, the intermediate loops applying skyhook strategy for the elimination of the disturbances, and the outermost loop using PID controller for the determination of the desired force. Some experiments were carried out on a physical test rig with a hardware-in-the-loops feature. The performance of the proposed control method was evaluated and benchmarked to examine the effectiveness of the system in suppressing the disturbance effect of the suspension system. It was found that the experimental results demonstrate the superiority of the active suspension system with Skyhook-PID scheme compared to the PID and passive suspension systems.